The rank and position of women in the commentary of Sheikh Khal - نەژاد, پ.ی د. عبدوڵڵا ڕەسووڵ; Mahmoudi, Saadat (Sulaimani Journal for Humanities, 2023)
Sheikh Mohammed Khal, as a Kurdish Muslim philanthropist, has devoted all his efforts to the people, religion and language. By writing dictionaries and proverbs, as well as reviving the works of Kurdish scholars such as Betooshi, Nodi and Zahavi, he paid attention to the language and culture of his people and fulfilled his national duty; He has fulfilled his religious duty by writing valuable works in the field of Islamic thought such as the commentary on the Holy Qur'an. Khal, who was a lover of the Qur'an and a butterfly from the beginning, believed that the best thing for himself and his people was to interpret the Qur'an in Kurdish so that everyone could benefit from it. One of the most valuable works of Mamoste Khalo is in terms of the significant innovative intellectual interpretations of the Islamic world. He has looked at contemporary innovative issues. One of these important issues is the bold defense of women's rights and the clear position of women in Islam's interpretation; For example, in the commentary on verse 228 of Surah Al-Baqarah, after referring to the views of Shaykh Muhammad 'Abda and Sayyid Qutb, he talks about equal rights for men and women In his interpretation of verse 8 of Surah Tahrim, he advocates equal responsibility of parents in the home and dozens of other such issues. In this article, we will present some important points about the position of women in Mamoste Khal's commentary in order to show his innovation in this sensitive field.
Keywords: Khal Master; Interpretation of the Holy Quran; The Position of Women; Innovation